2018
DOI: 10.1257/pol.20150116
|View full text |Cite
|
Sign up to set email alerts
|

From Selling Goods to Selling Services: Firm Responses to Trade Liberalization

Abstract: In this paper, we focus on a new channel of adaptation to trade liberalization, namely the shift toward increased provision of services in lieu of goods production. We exploit variation in European Union trade policy to show that lower manufacturing tariffs lead firms to shift into services provision and out of goods production. We also find that a successful transition is associated with higher firm-level R&D stocks. (JEL D22, F13, F14, L16, L60, L80)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 37 publications
1
39
1
3
Order By: Relevance
“…They found that lower manufacturing tariffs lead firms to shift into service provision and out of goods production, and selling industry‐specific expertise and specialising in skill‐intensive services production are two main mechanisms. In contrast to Breinlich et al (), we find that, China's input liberalisation results in a decline of MS by incurring larger goods import and less share of service import.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…They found that lower manufacturing tariffs lead firms to shift into service provision and out of goods production, and selling industry‐specific expertise and specialising in skill‐intensive services production are two main mechanisms. In contrast to Breinlich et al (), we find that, China's input liberalisation results in a decline of MS by incurring larger goods import and less share of service import.…”
Section: Introductioncontrasting
confidence: 99%
“…One is research on input trade liberalisation, covering the impact of input liberalisation on productivity (Amiti & Konings, 2007;Brandt et al, 2017), export prices and quality upgrading (Bas & Strauss-Kahn, 2015), firm export decisions and downstream firm exports (Bas, 2012;Chevassus-Lozza, Gaigné, & Le Mener, 2013), firm innovation (Fan, Li, & Yeaple, 2015;Liu & Qiu, 2016), etc. It is worth mentioning that Breinlich, Soderbery, and Wright (2018) studied the impact of trade liberalisation on the services provided by UK manufacturing firms which is the only one study directly relevant to our paper. They found that lower manufacturing tariffs lead firms to shift into service provision and out of goods production, and selling industry-specific expertise and specialising in skill-intensive services production are two main mechanisms.…”
Section: F I G U R Ementioning
confidence: 99%
“…These estimates, which confirm the ambiguity of the evidence reported in the existing literature, are partly driven by the fact that such econometric analysis gives great importance to the evolution of the performance of firms that drastically changed their business models, moving from very low shares of services to very large shares. 15 Breinlich et al (2014) provide empirical evidence in favor of such a defensive strategy. They show that increasing competition pressure resulting from lower European manufacturing tariffs caused British firms to shift into the provision of services and out of the production of goods.…”
Section: N O T E Smentioning
confidence: 99%
“…Breinlich et al. () provide empirical evidence in favor of such a defensive strategy. They show that increasing competition pressure resulting from lower European manufacturing tariffs caused British firms to shift into the provision of services and out of the production of goods.…”
mentioning
confidence: 99%
“… There also exist alternative explanations: Breinlich et al () explore the shift to producing services by manufacturing firms in response to increased trade liberalization. Lancheros and Demirel () study the relationship between access to finance and service exports in India.…”
mentioning
confidence: 99%